Excel models for business and operations management - Barlow, John F. (Chichester : John Wiley and Sons, 1999)
A systems view of business. Model-building tools. Financial models. Worksheet applications in cost accounting. Marketing models. Purchase order processing: a database application.
Keywords: Microsoft Excel; Computer programs; Microsoft Excel (Computer file); Business -- Mathematical models -- Computer programs; Business -- Decision making -- Mathematical models -- Computer programs